2022
DOI: 10.2196/29780
|View full text |Cite
|
Sign up to set email alerts
|

Health Professionals’ eHealth Literacy and System Experience Before and 3 Months After the Implementation of an Electronic Health Record System: Longitudinal Study

Abstract: Background The implementation of an integrated electronic health record (EHR) system can potentially provide health care providers with support standardization of patient care, pathways, and workflows, as well as provide medical staff with decision support, easier access, and the same interface across features and subsystems. These potentials require an implementation process in which the expectations of the medical staff and the provider of the new system are aligned with respect to the medical st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…The characteristics of the included studies are presented in Table 2 . Thirteen of the publications used a cross-sectional design [ 25 – 37 ], and one used a longitudinal design with two cross-sectional samples [ 38 ]. The latter study assessed eHealth literacy before and after the implementation of an integrated electronic health record (HER) system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the included studies are presented in Table 2 . Thirteen of the publications used a cross-sectional design [ 25 – 37 ], and one used a longitudinal design with two cross-sectional samples [ 38 ]. The latter study assessed eHealth literacy before and after the implementation of an integrated electronic health record (HER) system.…”
Section: Resultsmentioning
confidence: 99%
“…The other studies included did not assessed eHealth literacy based on a particular type of eHealth source or resource. The publications included were conducted in Ethiopia [ 27 , 33 35 ], Turkey [ 25 , 36 , 37 ], South Korea [ 30 , 31 ], Denmark [ 38 ], Iran [ 26 , 28 ] and Greece [ 32 ] over a period from 2015 to 2021 (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has suggested digital competency to be important for healthcare providers’ uptake and use of electronic healthcare services [ 37 ]. Furthermore, the implementation of a patient portal, including sharing access with patients, did not in itself increase healthcare providers’ digital competency [ 38 ]. Hence, as requested by some informants, support from the management with training in patient portal use and forums for collegial discussions appear important for healthcare providers’ adoption and use of patient portals including sharing clinical notes and using telehealth.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has suggested digital competency to be important for healthcare providers´ uptake and use of electronic healthcare services (36). Furthermore, the implementation of a patient portal, including sharing access with patients, did not in itself increase healthcare providers' digital competency (37). Hence, as requested by some informants, support from the management with training in patient portal use and forums for collegial discussions appear important for healthcare providers' adoption and use of patient portals including sharing clinical notes and using telehealth.…”
Section: Digital Competencymentioning
confidence: 99%